PERSEPSI DAN PREFERENSI PENGHUNI PERMUKIMAN DI SEMPADAN SUNGAI INDRAGIRI DAN ASPIRASI MASYARAKAT KECAMATAN TEMBILAHAN HULU KABUPATEN INDRAGIRI HILIR, RIAU - Siti Agre Esa; Denny Helard; Rizki Aziz (Rang Teknik Journal, 2026)
Settlements on river borders are generally associated with the need for land for commercial and residential activities, resulting in changes in land function in various areas. The aim of this research is to determine and analyze the perceptions and preferences of residents in the Indragiri River border area and the aspirations of the people of Kec. Tembilahan Hulu as well as knowing and analyzing the influencing factors and dominant factors on the perceptions and preferences of residential residents. The sampling technique used was purposive sampling and the data collection method was by distributing questionnaires directly to respondents using a quantitative method approach. Data analysis uses the respondent achievement level (TCR) and confirmatory factor analysis approaches. The dominant factor for perception is government regulations with a cumulative factor value of 36.44% and the dominant factor in the preferences of residents of settlements along the river is personal interests with a cumulative value of 75.88%. The community aspirations conveyed by several communities that live outside the river border area are that settlements on the river border must receive special attention from the government and have regulations that are right on target and the government can pay attention to their livelihood factors which are related to the community's own economy.Keywords: Settlements, rivers, riverbanks, perceptions, preferences